Influence of Supraglacial Debris Thickness on Thermal Resistance of the Glaciers of Chandra Basin, Western Himalaya - Patel, Lavkush Kumar; Sharma, Parmanand; Singh, Ajit; Oulkar, Sunil; Pratap, Bhanu; Thamban, Meloth (Frontiers in Earth Science, 2021)
A large number of glaciers in the Hindu-Kush Himalaya are covered with debris in the lower part of the ablation zone, which is continuously expanding due to enhanced glacier mass loss. The supraglacial debris transported over the melting glacier surface acts as an insulating barrier between the ice and atmospheric conditions and has a strong influence on the spatial distribution of surface ice melt. We conducted in-situ field measurements of point-wise ablation rate, supraglacial debris thickness, and debris temperature to examine the thermal resistivity of the debris pack and its influence on ablation over three glaciers (Bara Shigri, Batal, and Kunzam) in Chandra Basin of Western Himalaya during 2016-2017. Satellite-based supraglacial debris cover assessment shows an overall debris-covered area of 15% for Chandra basin. The field data revealed that the debris thickness varied between 0.5 and 326 cm, following a spatially distributed pattern in the Chandra basin. The studied glaciers have up to 90% debris cover within the ablation area, and together represent ~33.5% of the total debris-covered area in the basin. The supraglacial debris surface temperature and near-surface air temperature shows a significant correlation (r = >0.88, p = < 0.05), which reflects the effective control of energy balance over the debris surface. The thermal resistivity measurements revealed low resistance (0.009 ± 0.01 m2 °C W-1) under thin debris pack and high resistance (0.55 ± 0.09 m2 °C W-1) under thick debris. Our study revealed that the thickness of supraglacial debris significantly retards the glacier ablation due to its high thermal resistivity.